All‐Metal Antiaromaticity in Sb4‐Type Lanthanocene Anions. Issue 18 (8th April 2016) - Min, Xue; Popov, Ivan A.; Pan, Fu‐Xing; Li, Lei‐Jiao; Matito, Eduard; Sun, Zhong‐Ming; Wang, Lai‐Sheng; Boldyrev, Alexander I.
Abstract: Antiaromaticity, as introduced in 1965, usually refers to monocyclic systems with 4 n π electrons. This concept was extended to all‐metal molecules after the observation of Li3 Al4 − in the gas phase. However, the solid‐phase counterparts have not been documented to date. Herein, we describe a series of all‐metal antiaromatic anions, [Ln( η 4 ‐Sb4 )3 ] 3− (Ln=La, Y, Ho, Er, Lu), which were isolated as the K([2.2.2]crypt) salts and identified by single‐crystal X‐ray diffraction. Based on the results obtained from the chemical bonding analysis, multicenter indices, and the electron‐counting rule, we conclude that the core [Ln( η 4 ‐Sb4 )3 ] 3− fragment of the crystal has three locally π‐antiaromatic Sb4 fragments. This complex represents the first locally π‐antiaromatic all‐metal system in the solid state, which is stabilized by interactions of the three π‐antiaromatic units with the central metal atom. Abstract : Several unique lanthanocene compounds, [Ln(η 4 ‐Sb4 )3 ] 3− (Ln=La, Y, Ho, Er, or Lu), were isolated as the K([2.2.2]crypt) salts and characterized by single‐crystal X‐ray diffraction. They feature a central lanthanide atom coordinated by three rhombic Sb4 units. Chemical bonding analysis revealed all three cyclo ‐Sb4 units in [Ln(η 4 ‐Sb4 )3 ] 3− to be locally π‐antiaromatic.